The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/nar/gkn372
|View full text |Cite
|
Sign up to set email alerts
|

Survey of group I and group II introns in 29 sequenced genomes of the Bacillus cereus group: insights into their spread and evolution

Abstract: Group I and group II introns are different catalytic self-splicing and mobile RNA elements that contribute to genome dynamics. In this study, we have analyzed their distribution and evolution in 29 sequenced genomes from the Bacillus cereus group of bacteria. Introns were of different structural classes and evolutionary origins, and a large number of nearly identical elements are shared between multiple strains of different sources, suggesting recent lateral transfers and/or that introns are under a strong sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 88 publications
3
60
0
Order By: Relevance
“…Phylogenetic analysis of the most frequently observed intron S1396, a group II intron, revealed that it was probably acquired both vertically and horizontally within the family. This feature is well known among group II introns (46)(47)(48)(49). Comparative sequence analysis of intron S1396 generally reflects the phylogeny suggested by 16S rRNA sequence analysis at species level (Table S1 and Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Phylogenetic analysis of the most frequently observed intron S1396, a group II intron, revealed that it was probably acquired both vertically and horizontally within the family. This feature is well known among group II introns (46)(47)(48)(49). Comparative sequence analysis of intron S1396 generally reflects the phylogeny suggested by 16S rRNA sequence analysis at species level (Table S1 and Fig.…”
Section: Discussionsupporting
confidence: 72%
“…In bacteria, group I and group II introns are small mobile elements (0.2 to 1 kb and 0.7 to 3 kb, respectively) that are transcribed into self-splicing RNAs (147,148). These introns are widespread within the bacterial kingdom but not very abundant.…”
Section: Inteins Introns and Retroelementsmentioning
confidence: 99%
“…By contrast, bacteriophages have a global gene pool with intense horizontal exchange occurring among genetically related local groups of phages and low-grade exchange of sequences occurring over wide phylogenetic distances (34), making them ideal vehicles for the transfer of HEs, introns, and inteins between phages, among bacteria, and between phages and bacteria. Further, in lysogeny the prophage provides a silent locus from which HEs can invade homologous host genes in bacteria (108). Introns and inteins also tend to target conserved genes that have both phage and bacterial copies, making insertions less toxic and improving the odds of homologous recombination (59,77).…”
Section: Disparate Origins Convergent Parasitic Strategiesmentioning
confidence: 99%
“…Increasingly, they are being found in a variety of protein-coding genes, including those for recombinase A and ribonucleotide reductase (77,108). In bacteriophages, they are seen both in tRNA genes and in some proteincoding genes, like those for DNA polymerase, ribonucleotide reductase, and thymidylate synthase (45).…”
Section: Group I Intronsmentioning
confidence: 99%